Asymptotic Expansion of the Moments of Correlogram Estimator for the Random-Noise Covariance Function in the Nonlinear Regression Model - Ivanov, O. V.; Moskvychova, K. K. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We establish asymptotic expansions of the bias, mean-square deviation, and variance for the correlogram estimator of the unknown covariance function of a Gaussian stationary random noise in the nonlinear regression model with continuous time.